2007
DOI: 10.2220/biomedres.28.119
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the endocrine and immune systems by well-controlled hyperthermia equipment

Abstract: Since high levels of hyperthermia induce immunosuppression to a certain extent (i.e., granulocytosis and lymphocytopenia) in patients, we applied mild hyperthermia in volunteers using equipment enabling well-controlled hyperthermia. Restricted control of rectal temperature at 39.4 (± 0.2)°C for 30 min was conducted and various parameters of the body were examined. The most prominent change observed during exposure to hyperthermia was elevated levels of pH and PO 2 in the blood, even in the venous blood. A tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
3
12
0
Order By: Relevance
“…4). served, due to the increase of PO 2 and sO 2 as seen in our previous studies (10,18,23). Of interest was the change in RBC conformation (Fig.…”
Section: Levels Of Catecholamines (Adrenaline Noradrenaline and Dopasupporting
confidence: 68%
“…4). served, due to the increase of PO 2 and sO 2 as seen in our previous studies (10,18,23). Of interest was the change in RBC conformation (Fig.…”
Section: Levels Of Catecholamines (Adrenaline Noradrenaline and Dopasupporting
confidence: 68%
“…In an earlier study, we showed that hyperthermia at the level up to 39.5°C (rectal temperature) for 30 min did not induce granulocytosis but rather induced immunopotentiation (14). In the present study, we applied this condition of hyperthermia for 6 cancer patients.…”
mentioning
confidence: 62%
“…In addition to immunosuppression of lymphocytopenia, these conditions finally induce the onset of malignancy, namely, the external causes of cancer. In the course of these studies, we have applied hyperthermia and noticed that high temperature of hyperthermia (i.e., > 40°C) induced thermal stress rather than immunopotentiation (14). The maximum condition might be 39.5°C of rectal temperature for but that was low in Case 3 and 5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations